Red Light, Purple Light! Results of an Intervention to Promote School Readiness for Children From Low-Income Backgrounds - McClelland, Megan M.; Tominey, Shauna L.; Schmitt, Sara A.; Hatfield, Bridget E.; Purpura, David J.; Gonzales, Christopher R.; Tracy, Alexis N. (Frontiers in Psychology, 2019)
Considerable research has examined interventions that facilitate school readiness skills in young children. One intervention, Red Light, Purple Light Circle Time Games (RLPL;Tominey and McClelland, 2011; Schmitt et al., 2015), includes music and movement games that aim to foster self-regulation skills. The present study (N = 157) focused on children from families with low-income and compared the RLPL intervention (SR) to a revised version of RLPL that included literacy and math content (SR+) and a Business-As-Usual (BAU) control group. In both versions of the intervention, teachers were trained to administer the self-regulation intervention in preschool classrooms with coaching support. Although not statistically significant, children receiving either version of the intervention gained more in self-regulation on the Head-Toes-Knees-Shoulders (HTKS) over the preschool year compared to the BAU group (β = 0.09, p = 0.082, Cohen’s d = 0.31). Effect sizes were similar to previous studies (Schmitt et al., 2015; Duncan et al., 2018) and translated to a 21% difference in self-regulation over and above the BAU group at post-test. Furthermore, children participating in either version of the intervention gained significantly more in math across the school year compared to children in the BAU group (β = 0.14; p = 0.003, Cohen’s d = 0.38), which translated to a 24% difference in math over and above the BAU group at post-test. Results were somewhat stronger for the SR+ version, although effect sizes across intervention conditions were comparable. There were no statistically significant differences across groups for literacy skills. Results extend previous research and suggest that the RLPL intervention, which includes an explicit focus on self-regulation through music and movement games, may improve children’s self-regulation and math scores over the preschool year.